Familial opposable triphalangeal thumbs associated with duplication of the big toes. Issue 1 (February 1985) - Merlob, P; Grunebaum, M; Reisner, S H
Abstract : A rare association of triphalangeal thumbs and duplication of the big toes is described. The family pedigree confirms autosomal dominant inheritance with marked penetrance. A systematic approach to the diagnosis of this anomaly is presented. The distinction between the two types of triphalangeal thumb, true (opposable) and finger-like (non-opposable), is emphasised.